Respon Vanuatu Terhadap Konflik Kekerasan dan Pelanggaran Hak Asasi Manusia Di Papua - Nujud, Yasub Atsyir (BULETIN ADALAH, 2021)
This research aims to provide a depiction of two views, namely about Vanuatu's role in West Papua's independence and addressing the problems that occur in West Papua related to violence and human rights. Specifically, this study aims to find out (a.) the response provided by the United Nations Human Rights Commission. The research method that the author uses in achieving the purpose of this research is with descriptive research methods with the technique of collecting data through literature studies sourced from books, journals, documents, and valid websites. The results of this study explain how the mass media itself in providing and presenting news to the audience related to the existing responses related to the desire for independence of West Papua from NKRI and how the world responds to human rights-related problems.